The Effect of 0.01% Atropine Eye Drops on the Ocular Surface in Children for the Control of Myopia—The Primary Results from a Six-Month Prospective Study - Cheng J; Yang Y; Kong X; Zeng L; Chen Z; Xu J; Zhang C (Dove Medical Press, 2020)
Jingyi Cheng,1– 3,* Yujing Yang,1– 3,* Xiehe Kong,4 Li Zeng,1– 3 Zhi Chen,1– 3 Jianjiang Xu,1– 3 Chaoran Zhang1– 3 1Department of Ophthalmology and Visual Science, Eye, Ear, Nose and Throat Hospital, Shanghai Medical College of Fudan University, Shanghai, People’s Republic of China; 2Key Laboratory of Myopia, Ministry of Health (Fudan University), Shanghai, People’s Republic of China; 3Shanghai Key Laboratory of Visual Impairment and Restoration (Fudan University), Shanghai, People’s Republic of China; 4Shanghai Research Institute of Acupuncture and Meridian, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chaoran ZhangDepartment of Ophthalmology and Visual Science, Eye, Ear, Nose and Throat Hospital, Shanghai Medical College of Fudan University, 83 Fenyang Road, Shanghai 200031, People’s Republic of ChinaTel/ Fax +86 2164377134Email zhangchaoran@hotmail.comPurpose: To evaluate the effect of 0.01% atropine eye drops on the ocular surface in children for the control of myopia.Methods: A total of 72 participants were recruited for this prospective study. Prior to and after 1, 3, and 6 months of 0.01% atropine administration, an ocular surface disease index (OSDI) questionnaire was obtained, Keratograph 5M was used for the measurement of the tear meniscus height (TMH), noninvasive keratographic tear film break-up time (NK-BUT, the first keratographic break-up time, [NK-BUTfirst] and the average keratographic break-up time, [NK-BUTave]), bulbar redness (BR), meiboscore (MS), and anterior segment optical coherence tomography (AS-OCT) was used to calculate the inferior tear meniscus area (TMA).Results: After using the 0.01% atropine eye drops for 1 month, 9 subjects complained of discomfort immediately after administration, but this quickly subsided, and 1 subject was temporarily dazzled. All the ocular surface symptoms were mild and occurred rarely. After 3 months, these complaints no longer occurred. Compared with the baseline values, the OSDI scores (0.08 ± 0.28), values of TMH (0.23 ± 0.04 mm), TMA (0.0420 ± 0.0444 mm2), NK-BUTfirst (9.39 ± 5.25 s), NK-BUTave (10.49 ± 4.94 s), BR (0.63 ± 0.37), and MS (0.89 ± 0.70) did not change significantly after 6 months of 0.01% atropine eye drop administration (P > 0.05).Conclusion: In this 6-month prospective study, no side effects were observed on the ocular surface after using 0.01% atropine in children.Keywords: 0.01% atropine eye drops, ocular surface, children, myopia control